ФОРМУВАННЯ ОСЕРЕДКІВ ХУДОЖНЬОЇ ОСВІТИ НА ЛІВОБЕРЕЖНІЙ УКРАЇНІ В XIX СТОЛІТТІ (Педагогіка вищої та середньої школи, 2001)
The article touches upon the problem of the formation of artistic education in the XIX century in the region mentioned above on different levels: in schools providing general education and gymnasiums, in universities and private schools. Here is represented a short essay about the art activities of the most famous teachers, which is based on traditions of academic education. Here is also the conclusion about the availability of conditions for the valuable high artistic education in Ukraine by the beginning of the The XX century is grounded.